Influence of rat progenitor neurogenic cells supernatant on glioma 101.8 cells in vitro - Liubich, L.D.; Semenova, V.M.; Stayno, L.P. (Вiopolymers and Cell, 2015)
Aim. To evaluate the influence of the rat progenitor neurogenic cells supernatant (RPNS) on the transplantable rat malignant brain glioma cells (strain 101.8) under conditions of cultivation. Methods. Primary cultures were obtained from glioma 101.8 fragments (n = 12) and intact brain of newborn rats (n = 9). RPNS was received from neurogenic cell suspensions of fetal rat brain on 8–11th (E8-11) and 12–16th (E12-16) days of gestation. Results: RPNS (E8-11) as well as RPNS (E12-16) showed a cytotoxic effect on the glioma 101.8 cells in short-term cultures, the level of which was dose-dependent and intensified with increasing duration of incubation. RPNS (E12-16) had a more pronounced cytotoxic action on the cells of glioma 101.8 compared with RPNS (E8-11). The cytotoxic index (CI) of RPNS (E12-16) on the glioma 101.8 cells was significantly higher than CI determined in cell suspensions of normal rat brain (CI was (91.99 ± 2.37) % and (22.9 ± 4.97) % respectively over 48 h incubation with RPNS). After RPNS (E8-11) influence on the glioma 101.8 primary cultures the signs of dose-dependent cytotoxic effects were observed: the thinning of growth areas, appearance of dystrophic and necrobiotic changes in tumor cells and decreasing of a mitotic index. These features were strengthened under the RPNS (E12-16) influence. Conclusions. Fetal RPNS showed dose-dependent cytotoxic and antiproliferative effects on the cultivated glioma 101.8 cells, which were intensified with the increasing of rat brain gestational age and lengthening of the incubation duration. A prerequisite for such effects is likely the NPC ability to produce the substances with antitumor activity.